ANÁLISE DE LESÕES DESPORTIVAS EM JOVENS PRATICANTES DE FUTSAL - Franciele Marques Vanderlei; Fábio do Nascimento Bastos; Rubens Vinicius Caversan Vidal; Luiz Carlos Marques Vanderlei; Jayme Netto Júnior; Carlos Marcelo Pastre (Colloquium Vitae, 2010)
The aim was to characterize sports injuries and explore risk factors for installation sports injuries in young football players. The data were collected from 86 young football players from the application of a Referred Condition Inquiry, adapted to the characteristics of the sport, with information related to the training season of approximately 12 months. The Referred Condition Inquiry contained data on demographics and training of players, who were the risk factors analyzed in addition to information on sports injuries as anatomical site, mechanism, moment, gravity, return to normal activities and recurrence. For statistical analysis, were used the Student t test for continuous variables or Mann Whitney test for discrete variables, and descriptive statistics and findings were discussed considering 5% statistical significance. The anatomic sites most affected were the lower limbs, with the mechanism for installation injuries more frequent being out of touch. The injuries occurred mainly during training and were of mild severity. Furthermore, 62.5% of the athletes returned to normal activities asymptomatic and 62.5% of injuries were not considered recurrences. With regard to risk factors showed no statistical difference between athletes affected and nonaffected for injuries. We conclude that young football players have a higher frequency of lower limb injuries, the mechanism without contact, during training, of mild severity, with return asymptomatic and not recurrent. There were no risk factors for its development of sports injuries.